Contribution of the oxygen reduction reaction to the electrochemical cathodic partial reaction for Mg-Al-Ca solid solutions - Felten, Markus; Zhang, Siyuan; Changizi, Rasa; Scheu, Christina; Bruns, Mark; Strebl, Michael; Virtanen, Sannakaisa; Zander, Daniela (Electrochemistry Communications, 2023)
The electrochemical corrosion rate of magnesium depends on the stability of the surface layer formed. Based on the Mg substrate, the oxide structure comprises a dense MgO/Mg(OH)2 mixture underneath a porous plate-like Mg(OH)2 layer. While the kinetics of the anodic partial reaction have been mainly attributed to MgO, recent studies have showed an effect of the Mg(OH)2 layer thickness on the cathodic partial reaction. A thinner Mg(OH)2 layer has been associated with higher kinetics of the oxygen reduction reaction. In the present study, the mechanism has been further investigated via in situ respirometric measurements using Mg-Al-Ca solid solution in electrolytes with different pH values (pH = 8.0–13.0). The results indicate an additional effect based on the structure of the surface layer for Mg-Al-Ca alloys in the passive state. Furthermore, two different Al-enriched interfaces were observed and discussed in terms of their thermodynamic stability under alkaline immersion conditions.
CRIS-Team Scopus Importer:2023-07-28
Keywords: Corrosion; Interfaces; Magnesium; ORR; TEM

Correlating X-ray computed tomography observations with respirometric measurement of aluminium alloy 6063 corrosion under FeCl3 droplets - Mahmood, S.; Bruns, Mark; Gallagher, C.; Virtanen, Sannakaisa; Engelberg, D. L. (Corrosion Science, 2024)
Corrosion of aluminium alloy 6063-T6 with exposure to simulated steel corrosion products using ferric chloride droplets was investigated. Focus of these experiments was to understand the role of oxygen in the redox process; therefore, samples were exposed to standard atmospheric conditions as well as to oxygen-derived conditions. Respirometric measurements indicate that the hydrogen evolution reaction (HER) is the dominant cathodic reaction. Especially in the initial stages when the corrosion rates are the highest, the HER occurs almost exclusively. At the later stages the oxygen reduction reaction (ORR) barely takes over as the main cathodic reaction. The dissolved volumes and maximum corrosion depths determined with X-ray Computed Tomography (XCT) were more significant for those samples deprived of oxygen. The composition of iron-rich deposits formed consisted of magnetite and maghemite, supporting exposure conditions where reactions were deprived of oxygen.
CRIS-Team Scopus Importer:2023-12-22
Keywords: 6063; Aluminium corrosion; Atmospheric corrosion; Computed tomography; Deoxygenated; Respirometry; X-ray CT

Corrosion Resistance of Biodegradable Zinc Surfaces Enhanced by UV-Grafted Polydimethylsiloxane Coating - Pupillo, Davide; Bruns, Mark; Prado, Lucia; Di Franco, Francesco; Böhringer, David; Mazare, Anca Valentina; Goldmann, Wolfgang; Virtanen, Sannakaisa; Santamaria, Monica; Tesler, Alexander (ACS Biomaterials Science and Engineering, 2024)
Improved living conditions have led to an increase in life expectancy worldwide. However, as people age, the risk of vascular disease tends to increase due to the accumulation and buildup of plaque in arteries. Vascular stents are used to keep blood vessels open. Biodegradable stents are designed to provide a temporary support vessel that gradually degrades and is absorbed by the body, leaving behind healed blood vessels. However, biodegradable metals can suffer from reduced mechanical strength and/or inflammatory response, both of which can affect the rate of corrosion. Therefore, it is essential to achieve a controlled and predictable degradation rate. Here, we demonstrate that the corrosion resistance of biodegradable Zn surfaces is improved by electroless deposition of zinc hydroxystannate followed by UV-grafting with silicone oil (PDMS). Potentiodynamic polarization, electrochemical impedance spectroscopy, respiratory kinetic measurements, and long-term immersion in three simulated body fluids were applied. Although zinc hydroxystannate improves the corrosion resistance of Zn to some extent, it introduces a high surface area with hydroxyl units used to UV-graft PDMS molecules. Our results demonstrate that hydrophobic PDMS causes a 3-fold reduction in corrosion of Zn-based materials in biological environments and reduces cytotoxicity through the uncontrolled release of Zn ions.
CRIS-Team Scopus Importer:2024-07-26
Keywords: biodegradable metals; corrosion resistance; polydimethylsiloxane; UV-grafting; zinc

Coupling Respirometric HER and ORR Monitoring with Electrochemical Measurements - Strebl, Michael; Bruns, Mark; Virtanen, Sannakaisa (Electrochimica Acta, 2022)
An experimental setup for respirometric real-time monitoring of the kinetics of the H2 evolution reaction and the O2 reduction reaction coupled with electrochemical control is presented. Cathodic polarization of different metal electrodes was carried out to verify the accuracy, and sensitivity of this approach. It was found that the respirometric response was in excellent agreement with the applied electrical signal. Dissolution of H2 in the liquid phase can lead to a delayed detection of the evolved H2 in the gas phase. However, reducing the volume of electrolyte in the setup can diminish this lag in response time. The influence of H2 oxidation on reactive Pt and the generation of H2O2 on Au on the respirometric monitoring of cathodic reactions was investigated. Finally, the combined respirometric and electrochemical approach was applied to quantify dissolution of Al during cathodic polarization by relating the total cathodic charge with the electrical signal.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Cathodic corrosion; Electrode kinetics; HER and ORR real-time monitoring; Respirometric Method

Critical factors for photoelectrochemical and photocatalytic H-2 evolution from gray anatase (001) nanosheets - Qin, Shanshan; Denisov, Nikita; Zhou, Xin; Zdražil, Lukáš; Fehn, Dominik; Hwang, Imgon; Bruns, Mark; Kim, Hyesung; Meyer, Karsten; Schmuki, Patrik (JPhys Energy, 2022)
In recent years, the defect engineering of titania via reduction treatments has shown a high potential for enabling efficient and co-catalyst-free photocatalytic H-2 generation from methanol/water solutions. However, defect engineering simultaneously alters several properties of TiO2. Here, we use pristine (white) and hydrogenated (gray) anatase nanosheets with dominant (001) facets. By comparing electrical conductivity, photocurrent spectra, transient photocurrent response, and photocatalytic H-2 evolution, we show that the increased conductivity or broad visible light absorption of gray titania is not responsible for its increased activity. Instead, the true bottleneck is the hole transfer rate that is significantly accelerated while using gray instead of white modification. Moreover, the hole transfer reaction causes the accumulation of the reaction products in pure water, hindering the photocatalytic H-2 evolution over time. These combined factors explain the superior performance of gray titania over white titania in photoelectrochemical or photocatalytic water splitting.
CRIS-Team WoS Importer:2022-10-07

Editors' Choice-Respirometric in Situ Methods for Real-Time Monitoring of Corrosion Rates: Part I. Atmospheric Corrosion - Strebl, Michael; Bruns, Mark; Virtanen, Sannakaisa (Journal of The Electrochemical Society, 2020)
A novel respirometric approach to monitor atmospheric corrosion kinetics is presented. Simultaneous real-time monitoring of the H-2 evolution reaction (HER) and the O-2 reduction reaction (ORR) is possible with a combination of optical O2 sensor measurements with gravimetric volume sensitive techniques or pressure sensor based techniques in closed chambers. The respirometric method is a universal, non-destructive tool applicable to any metal or alloy. It shows a high sensitivity for low corrosion rates and has a high time-resolution. Different examples of relevant engineering metals and alloys will be provided. Mass loss validation measurements carried out at the end of exposure show a good correlation with the total recorded cathodic charge. For metals with different oxidation states the average valency in the corrosion products can be calculated from the cathodic charge together with mass loss. The versatility of the novel monitoring technique is further demonstrated by studying the influence of wet-dry cycling, temperature steps or changes in the gas composition in situ. The rate of HER, ORR and total corrosion rate during these changing exposure conditions can be tracked directly on the same sample. Overall the new method contributes to bridging the gap between lab tests, accelerated testing and field exposure. (C) 2020 The Author(s). Published on behalf of The Electrochemical Society by IOP Publishing Limited.
CRIS-Team WoS Importer:2020-03-13

Long-term stability of aerophilic metallic surfaces underwater - Tesler, Alexander; Kolle, Stefan; Prado, Lucia; Thievessen, Ingo; Böhringer, David; Backholm, Matilda; Karunakaran, Bhuvaneshwari; Nurmi, Heikki A.; Latikka, Mika; Fischer, Lena; Stafslien, Shane; Cenev, Zoran M.; et al. (Nature Materials, 2023)
Aerophilic surfaces immersed underwater trap films of air known as plastrons. Plastrons have typically been considered impractical for underwater engineering applications due to their metastable performance. Here, we describe aerophilic titanium alloy (Ti) surfaces with extended plastron lifetimes that are conserved for months underwater. Long-term stability is achieved by the formation of highly rough hierarchically structured surfaces via electrochemical anodization combined with a low-surface-energy coating produced by a fluorinated surfactant. Aerophilic Ti surfaces drastically reduce blood adhesion and, when submerged in water, prevent adhesion of bacteria and marine organisms such as barnacles and mussels. Overall, we demonstrate a general strategy to achieve the long-term stability of plastrons on aerophilic surfaces for previously unattainable underwater applications.
CRIS-Team Scopus Importer:2023-09-29

Modification of in vitro degradation behavior of pure iron with ultrasonication treatment: Comparison of two different pseudo-physiological solutions - Zhou, Juncen; Fink, Michael; Bruns, Mark; Yang, Yuyun; Detsch, Rainer; Boccaccini, Aldo R.; Ermert, Helmut; Virtanen, Sannakaisa (Materials Science and Engineering C, 2018)

Multi-Method Approach to Assess the Corrosion Behavior of a Coated WE43 Mg Alloy - Höhlinger, Michael; Bruns, Mark; Dahlem, Lukas; Virtanen, Sannakaisa (Corrosion, 2021)
Developing appropriate and functional coatings for Mg alloys, such as WE43, in view of controlling the degradation rate in biodegradable applications, requires a realistic understanding of the corrosion processes. While conventional methods, such as electrochemical measurements, can already give a good estimation about the protectiveness of coatings, immersion tests are also required to simulate a more realistic corrosion scenario (i.e., open-circuit dissolution as a function of time). In the current study, immersion tests at pH 5 were performed in a solution composed of the inorganic Dulbecco's Modified Eagle's Medium constituents. For four different types of coatings on WE43, a combined experimental approach was introduced that compares the corrosion rates obtained by the different methods. The strengths and drawbacks of the methods, such as hydrogen evolution and ion release measurements, mass loss, and electrochemical tests, will be discussed. The different monitoring methods all have their advantages; thus, for a profound examination, multiple methods should be used in a complementary manner. For the evaluation of the corrosion protection ability of coated samples, the hydrogen evolution measurements may offer the most advantages.
CRIS-Team WoS Importer:2021-03-26

Overcoming Temperature-Induced Degradation of Silver Nanowire Electrodes by an Ag@SnOx Core-Shell Approach - Kalancha, Violetta; These, Albert; Vogl, Lilian; Levchuk, Ievgen; Zhou, Xin; Barr, Maissa; Bruns, Mark; Bachmann, Julien; Virtanen, Sannakaisa; Spiecker, Erdmann; Osvet, Andres; Brabec, Christoph; et al. (Advanced Electronic Materials, 2022)
Transparent electrodes consisting of silver nanowires (Ag NWs) are a solution-processed alternative to commonly used indium tin oxide electrodes. Here, Ag NW electrodes protected by a tin oxide (SnOx) are explored and unprecedented thermal stability is found. While unprotected Ag NW electrodes fail at 250 degrees C, the SnOx Ag NW electrodes remain stable for 40 h at 250 degrees C and withstand high temperatures up to 500 degrees C for short times. First, an optimized method of synthesis that provides uniform Ag NWs with high reproducibility is used. Afterward, a SnOx shell is formed in a wet chemical reaction. Fabrication of highly conductive electrodes requires thermal annealing at 300 degrees C for 5 min under ambient atmosphere. Electrodes with a sheet resistance as low as 20 ohm sq(-1) and visible transmittance of 84% are demonstrated. It is shown that a approximate to 2 nm thick SnOx shell effectively protects the Ag NWs in a temperature range between 200 and 500 degrees C, whereas unprotected Ag NWs suddenly fail at temperatures beyond 200 degrees C. It is strongly anticipated that these improvements in the stability of Ag NWs open a large field of further investigations and applications.
CRIS-Team WoS Importer:2022-02-11

Radiolysis‐Driven Evolution of Gold Nanostructures – Model Verification by Scale Bridging In Situ Liquid‐Phase Transmission Electron Microscopy and X‐Ray Diffraction - Fritsch, Birk; Zech, Tobias; Bruns, Mark; Körner, Andreas; Khadivianazar, Saba; Wu, Mingjian; Zargar Talebi, Neda; Virtanen, Sannakaisa; Unruh, Tobias; Jank, Michael; Spiecker, Erdmann; Hutzler, Andreas (Advanced Science, 2022)
Utilizing ionizing radiation for in situ studies in liquid media enables unique insights into nanostructure formation dynamics. As radiolysis interferes with observations, kinetic simulations are employed to understand and exploit beam-liquid interactions. By introducing an intuitive tool to simulate arbitrary kinetic models for radiation chemistry, it is demonstrated that these models provide a holistic understanding of reaction mechanisms. This is shown for irradiated HAuCl4 solutions allowing for quantitative prediction and tailoring of redox processes in liquid-phase transmission electron microscopy (LP-TEM). Moreover, it is demonstrated that kinetic modeling of radiation chemistry is applicable to investigations utilizing X-rays such as X-ray diffraction (XRD). This emphasizes that beam-sample interactions must be considered during XRD in liquid media and shows that reaction kinetics do not provide a threshold dose rate for gold nucleation relevant to LP-TEM and XRD. Furthermore, it is unveiled that oxidative etching of gold nanoparticles depends on both, precursor concentration, and dose rate. This dependency is exploited to probe the electron beam-induced shift in Gibbs free energy landscape by analyzing critical radii of gold nanoparticles.<br
Keywords: critical radius; gold nanoparticles; kinetic modelling; liquid-phase transmission electron microscopy; oxidative etching; particle growth; radiolysis

Respirometric in Situ Methods for Real-Time Monitoring of Corrosion Rates: Part III. Deconvolution of Electrochemical Polarization Curves - Strebl, Michael; Bruns, Mark; Virtanen, Sannakaisa (Journal of The Electrochemical Society, 2023)
A highly sensitive respirometric method is presented that allows real-time monitoring of reaction rates involving H2 and O2 during electrochemical polarization. The measurement approach is based on simultaneous monitoring of the changes in the total pressure and the O2 partial pressure inside a closed chamber. Hence, it is possible to quantify the rates resulting from reactions such as HER, ORR and OER as a function of the applied potential. As a result, deconvolution of the net electric current into cathodic and anodic partial reaction rates during electrochemical polarization can be obtained. It was demonstrated that the respirometric monitoring approach can reveal superfluous cathodic reactions from Al during cathodic polarization as well as during anodic polarization of Al and Mg AZ31. Thus, the true metal oxidation rate could be determined from the electric current and the cathodic reaction rates. Furthermore, the rate of the HER during cathodic electrodeposition of Zn was measured. Through respirometric monitoring of Ni and stainless steel at high anodic potentials, the rate of O2 evolution could be distinguished from electrode oxidation processes.
CRIS-Team Scopus Importer:2023-06-23

Respirometric in situ methods for real-time monitoring of corrosion rates: Part II. Immersion - Strebl, Michael; Bruns, Mark; Schulze, G.; Virtanen, Sannakaisa (Journal of The Electrochemical Society, 2021)
With the aim to open a new window into corrosion processes this paper presents respirometric methods for real-time in situ monitoring of corrosion rates under immersion conditions. With these techniques, sensitive, non-destructive corrosion rate measurements are possible on basically all metals and alloys. Different methods are presented that enable to monitor HER, ORR or both reactions simultaneously based on the amount of evolved H2 or the amount of consumed O2 by volumetric, manometric and sensor-based approaches. Various research examples are presented, demonstrating the benefits and limitations of the different approaches. For Mg alloys, besides HER, ORR plays a role in the cathodic reactions and a good correlation of the total cathodic charge with mass loss was obtained. H2 dissolution into the electrolyte was identified as an important factor. The results obtained for Zn immersion corrosion in intermittent-flow and flow-through respirometric experiments suggest that the ORR mechanism leads to the generation of stable H2O2 under these conditions. As a result, the effective number of exchanged electrons for one O2 molecule was found to be in between two and four. The here introduced respirometric techniques allow new insights into corrosion mechanisms, in addition to enabling real-time monitoring of corrosion.
CRIS-Team Scopus Importer:2021-02-05